EFFECT OF THE CONTROL ROD POSITION ON CRITICALITY (S CURVE) SIMULATIONS USING THE SCALE COMPUTER CODE IN THE KARTINI REACTOR - Arif Isnaeni (Indonesian Journal of Physics and Nuclear Applications, 2019)
Abstract The Kartini Reactor has been operated up to 100 kilo watts. There are two types of nuclear fuel used in the Kartini Reactor, type 104 and type 204. Currently the nuclear fuel utilization license granted by BAPETEN allows 77 pieces, consisting of 73 type 104 and four type 204. Based on Kartini Reactor fuel utilization report, there are 71 pieces of nuclear fuel in the reactor core, consist of 69 type 104 and two pieces of type 204. There are four pieces of type 104 in the bulk shielding. The control rod categorizations are divided into regulating rod, shim rod and safety rod. Regarding the operation license renewal of Kartini Reactor, we conducted an assessment of various aspects related to the safety of the reactor. One of the aspects we conducted was regards to the neutronic. On the initial phase of the neutronic aspect study, a simulation was performed using the SCALE computer code. This study will only evaluate the relation between the bank of the control rod position to the effect of criticality in the Kartini Reactor. The results showed that fully up criticality has a value of 1.02173 ± 0.00018, and fully down criticality has value of 0.96026 ±0.00021. The reactor reaches criticality when the position of the control rod is at an altitude of 42.85135 cm.